Εἰκών bei Paulus - KÓKAI-NAGY, Viktor (Studia Universitatis Babes-Bolyai Theologia Reformata Transylvanica, 2022)
Εἰκών in Paul. “And God said, Let us make man in our image (ποιήσωμεν ἄνθρωπον κατ ̓ εἰκόνα ἡμετέραν)...” (Gen 1:26). One assumes that this meaningful phrase has left many traces in the New Testament. But if one looks at the occurrence of the word εἰκών, it becomes quite clear that it has a special theological meaning only for Paul. For him, the word expresses the extraordinary dignity of the human being. In my article I would like to explore this theme and compare Paul’s thoughts on εἰκών with Philo’s concept of εἰκών. In my article I would like to discuss the topic in three points. First, we will brief-ly look at the εἰκών motif in Genesis. Then we will see how Philo understood the image of God. And at the end we will arrive to Paul.